Simulação acústica de salas de aula em escolas de educação básica: uma proposta tipológica para prática musical - Brum, Cristhian Moreira (2012)
The study of room acoustics is linked to the importance of sound inside a room, so the architectural characteristics of the internal space determine the acoustic behavior. To get better acoustics of a room there are computational methods that simulate the acoustic behavior of a room before his execution, providing the prediction of the simulated environment behavior from the acoustic point of view. The acoustic parameters of the resulting acoustic simulations as Reverberation Time, Initial Decay Time, Clarity, Sharpness and Speech Transmission Index, are responsible for identifying the acoustic conditions of the geometric model of a classroom. This geometric model used as sample classrooms of different types of municipal schools in Santa Maria - RS, with the aim of developing a classroom typology for the music teaching from virtual acoustic models using computing simulation. Geometric models of classrooms for teaching music were developed using as input data, dimensions, shapes and elements usually used in these environments and developed representative virtual acoustic models these virtual classrooms, in which were measured acoustic parameters related to the reverberation time from the impulse response of the acoustic models of virtual rooms. We analyzed the experimental results and simulated with and without furniture for the acoustic parameters, and these comparisons were related to the values of JND (Just Noticeable Difference) near the standard tolerance according to ISO 3382/2009 with normalized values of 500 Hz to 1000 Hz. A geometric study was developed based on Bolt (1946) which defined the appropriate geometric measures of the room. Thus, a functional typology was originated which meets the architectural acoustic requirements and the initial proposal of presenting a music classroom typology providing an environment with acoustic quality, according to Law number 11.769/2008 that inserts education music in schools on a mandatory basis.